NONSELFADJOINT DEGENERATE DIFFERENTIAL OPERATOR EQUATIONS OF HIGHER ORDER ON INFINITE INTERVAL - Zschorn, S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2014)
In the paper the Dirichlet problem for some class of degenerate nonselfadjoint differential operator equations of higher order on the infinite interval are considered.Existence and uniqueness of the generalized solution of Dirichlet problem is proved, some analogue of the Keldysh theorem for the corresponding onedimensional operator is established.
Keywords: differential equations in abstract spaces, degenerate differential operator equations, weighted Sobolev spaces